2017
DOI: 10.1039/c7ra11069c
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous-phase flame retardant behavior of a multi-phosphaphenanthrene compound in a polycarbonate composite

Abstract: A multi-phosphaphenanthrene compound (TDBA) was incorporated into polycarbonate (PC) to prepare a flame retardant composite. TDBA improved the flame retardancy of the PC material effectively. The PC composite comprising 10 wt% TDBA passed the UL94 V-0 level with a LOI value of 33.7%. The incorporation of TDBA effectively inhibited the combustion intensity of the TDBA/PC composite via reducing the production of flammable methane and carbonyl-containing substances, suppressing the oxidative process of combustibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…The low char yield of the PBT/PLO blends suggested that the char formation might not be the main fire retarding mechanism. The reduction in the char yield and accelerated decomposition behavior was also reported for polycarbonate after incorporation with different amounts of phosphaphenanthrene FR 35 . The phosphorus compound presence in the PVO may have reacted with PBT, which converted it to a less flammable structure through chemical reactions or crosslinking 36 .…”
Section: Resultssupporting
confidence: 59%
“…The low char yield of the PBT/PLO blends suggested that the char formation might not be the main fire retarding mechanism. The reduction in the char yield and accelerated decomposition behavior was also reported for polycarbonate after incorporation with different amounts of phosphaphenanthrene FR 35 . The phosphorus compound presence in the PVO may have reacted with PBT, which converted it to a less flammable structure through chemical reactions or crosslinking 36 .…”
Section: Resultssupporting
confidence: 59%
“…CO 2 (2,362 and 2,308 cm −1 ), phenol derivative (3,654 cm −1 for C aromatic -OH, 3,013 and 1,508 cm −1 for C aromatic -H, 1,604 cm −1 for C aromatic = C aromatic , and 1,174 cm −1 for C aromatic -O), methane (2,997 and 1,302 cm −1 ), carbonyl-containing compound (1,235 cm −1 for C carbonyl -O and 1,788 cm −1 for C=O), para-disubstituted benzene and unsubstituted benzene (824 and 668 cm −1 ) are the dominating products of pure PC within 40 wt% mass loss. [25,47] For PC-13.5% A3 (Figure 10b), the disappearance of the peaks at 3,013, 2,997, 824 -, and 668 cm −1 within 5% mass loss indicates that the decomposition process of PC is delayed. This phenomenon suggests the combustion of PC is effectively inhibited.…”
Section: Tga-ftir and Py-gc/ms Analysis On Pc Compositesmentioning
confidence: 99%
“…The PC composites with 1% LaHPP and 7% DBDPO have an increased LOI value to 40.5% and reduce PHRR by 42.3%. Qiu [25] used a flame retardant named TDBA in PC materials. TDBA effectively suppresses the combustion intensity of the PC/TDBA composite due to its multi-phosphaphenanthrene groups, and exerts great flame retardant effect through the gaseous phase.…”
Section: Introductionmentioning
confidence: 99%
“…Polycarbonate (PC) is playing an important role in modern industries such as automobile industry, glass assembly, construction, electrical and electronic (E&E) by virtue of its outstanding performance including high mechanical strength, elastic coefficients, transparency and thermal stability [ 1 , 2 , 3 , 4 ]. Although PC has already demonstrated good flame retardant performance such as 25% limiting oxygen index (LOI) and V-2 rating for burning test (UL 94), it is still difficult to meet more stringent needs, especially in fast-growing vehicle and E&E industries [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%